Optimizing the Learning Process through Theory-based Media Selection: Constructivist, Cognitive, Collaborative, and Motivational Perspectives - Aldi, Muhammad; Azzahra, Fatimah; Aminullah, Muhammad; Susilawati, Samsul (SAINTIS Publishing, 2025)
The learning process is an important element in education, where learning media acts as a tool that helps deliver material effectively to learners. Learning media triggers students' interest, attention and engagement, which in turn can improve their motivation and learning outcomes. This paper discusses the classification of learning media based on the theoretical basis of their use, focusing on constructivist, cognitive, collaborative and motivational theories. Each of these approaches emphasizes different learning methods, ranging from active interaction with the material, deep information processing, to cooperation and motivation. In addition, this paper also outlines a variety of learning media, both technology-based and non-technology-based, that can be used to meet various instructional needs. The results of this study show that the selection of learning media in accordance with a particular learning theory can strengthen the effectiveness of the educational process and help students achieve optimal learning outcomes.